Simulation of Elliptical Liquid Jet Primary Breakup In Supersonic Crossflow. (5th June 2020) - Zhou, Yao-zhi; Xiao, Feng; Li, Qing-lian; Li, Chen-yang
Abstract : The study of elliptical liquid jets in supersonic flow in a Mach 2.0 is performed numerically. The primary breakup process of the elliptical liquid jet is simulated for a Weber number 223, liquid/gas flux momentum 4.0. The aspect ratios of elliptical geometries are set to be 0.25, 0.5, 1, 2, and 5. The results show a remarkable difference in liquid jet disintegration morphology at different aspect ratios. Under supersonic crossflow conditions, the elliptical liquid jet shows more breakup characteristics than the round liquid jet. As the aspect ratio grows, the penetration depth decreases. The elliptical liquid jet with AR = 0.25 has the largest penetration depth in all cases. Moreover, the round jet has a maximum spreading angle of 50.2°. The changing trends of the column breakup length both x direction and y direction are similar. The elliptical jet at a lower aspect ratio has a shorter breakup length due to the narrower windward area. The liquid jet has a pair of larger horseshoe vortex structure and a wider wake region at a higher aspect ratio. Two pairs of reversal vortex pairs with obvious characteristics can be observed in all the simulations.